Penerapan Algoritma SAW Dalam Menentukan Keputusan Kelulusan Siswa/i SMPN 6 Surade - Saprudin, Saprudin (UNIVED Press, 2022)
Abstract-State Junior High School 6 Surade is an educational institution that annually determines graduation where students complete all educational programs that have been followed by students. Determination of the graduation of students in junior high school 6 Surade has problems with the lack of accuracy in student assessments so that the results obtained do not match the predetermined criteria. With these problems, a technological system is designed, namely a decision support system that can provide solutions to problems in determining student graduation. The algorithm used to determine the graduation of students at the 6 Surade junior high school is by using the Simple Additive Weighting method by finding the weighted sum value of the rating value in performance on each alternative on each criterion, so that in this way it is able to produce the best, accurate, and best value. And fast and can make it easier for educational institutions in determining assessment decisions with more accurate and structured results.